Determinants of sexually transmitted infections among adolescent girls and young women in artisanal and small-scale mining communities of Uganda - Betty Kwagala; Hanna Chidwick; Deborah Mensah; John Bosco Asiimwe; Stephen Ojiambo Wandera; Miriam Mutabazi; Fred Ngabirano; Lydia Osei; Lydia Kapiriri (BMC Public Health)
Abstract Background The artisanal and small-scale mining (ASM) sector has become an important employer in mineral rich countries of sub Saharan Africa where women constitute up to half of the labour force. However, gender and socio-economic marginalization negatively impact the sexual and reproductive health (SRH) of the adolescent girls and young women (AGYW) who work in the ASM sector. Despite the growing literature on adolescents’ SRH, there is a paucity of literature on the SRH of this last mile population. This paper fills this gap in the literature by examining the prevalence and determinants of self reported sexually transmitted infection (STI) status among AGYW in the ASM gold mining sectors of Uganda. Methods The paper is based on 636 AGYW working in the mining sectors in Uganda who had ever had sex. Descriptive analysis involved frequency distributions and chi squared tests. Multivariable analysis involved fitting a binary logistic regression model to assess the determinants of self reported STI status of the AGYW. Results Almost half (47%) of the respondents had a self reported STI during the 12 months preceding the study. The odds of reporting an STI were higher among adult young women compared with minors (AOR = 3.35; 95% CI 1.82 – 6.16); AGYW with primary level of education compared to those with none (AOR = 2.89; 95% CI 1.24 – 6.75); who drank alcohol (AOR 1.59; 95% CI 1.06—2.39); and engaged in transactional sex (AOR 2.42; 95% CI 1.37 – 4.28). Conclusions The results highlight the urgent need to respond to the high prevalence of self reported STIs among AGYW in ASM. The risk factors constitute multiple and intersecting vulnerabilities that require both preventive and curative interventions targeting female and male ASM workers and host communities, with emphasis on behavioral change and promotion of viable alternative sources of income. The ministries of Health, Gender, Labour and Social Development and key development partners should adopt a multi sectoral approach that effectively engages key stakeholders, including mining host communities, given the close interrelations between gender, health and economic aspects of the AGYW’s lives.